Allium discoloration: the color-forming potential of individual thiosulfinates and amino acids: structural requirements for the color-developing precursors - Kubec, Roman; Velísek, Jan (Journal of agricultural and food chemistry, 2007)
Structural requirements for compounds involved in Allium discoloration have been investigated in detail. The abilities of all 20 protein amino acids and six naturally occurring 1-propenyl-containing thiosulfinates to form the pigments have been studied. Furthermore, several analogues of these thiosulfinates were prepared by synthesis, and their color-forming abilities were evaluated, together with those of various amino compounds. It has been found that an unsubstituted primary amino group and a free carboxyl group are essential structural features required for amino compounds to be able to generate the pigments. Out of the thiosulfinate analogues tested, only those containing at least a three-carbon chain with the beta-carbon bearing a hydrogen atom yielded the pigments after reacting with glycine. Thiosulfonates, sulfoxides, sulfides, and disulfides did not form any colored products when mixed with glycine. The pH optimum for pigment formation has been found to be between 5.0 and 6.0 for all thiosulfinates tested.
Keywords: Amino Acids; koncentrace vodíkových iontů; Color; biologické pigmenty; Sulfinic Acids; kyseliny sulfinové; Pigments, Biological; Allium; Hydrogen-Ion Concentration; barva; aminokyseliny